Multifunctional Electronic Textiles by Direct 3D Printing of Stretchable Conductive Fibers - Wang, Yuntian; Wang, Zhixun; Wang, Zhe; Xiong, Ting; Shum, Perry Ping; Wei, Lei (Advanced electronic materials, 2023)
The integration of functional fibers into wearable devices by traditional methods is commonly completed in weaving. A new post‐weaving method of integrating fiber devices into textiles is needed to address the challenge of incorporating functional fiber into ready‐made garments without tearing down the clothing and re‐weaving. A 3D printing method to simultaneously fabricate and integrate highly stretchable conductive fiber into ready‐made garments with designed patterns is presented. The fabricated sheath–core fiber consists of a styrene–ethylene–butylene–styrene (SEBS) shell and a Ga–In–Sn alloy liquid metal core. The SEBS shell guarantees the high stretchability (up to 600%) and flexibility, while the liquid metal core offers a high conductivity maintained at large deformation. It is shown that sophisticated patterns, which have millimeter‐level‐resolution that are difficult to be integrated into textiles by weaving, and even more laborious to be incorporated into ready‐made garments, can now be easily modified and implemented into both textiles and ready‐made garments by a time‐saving and low‐cost 3D printing method. Utilizing the electrical characteristics of the fiber in pre‐designed patterns, on‐clothing soft electronics can be printed directly. A printed on‐clothing strain sensor, bending sensor, wireless charging coil, and a touch‐sensing network are demonstrated to show the potential applications in wearable electronics. A 3D printing method is developed to simultaneously fabricate and integrate highly stretchable conductive fiber into ready‐made garments with designed patterns, achieving diverse functions, for example, a printed on‐clothing wireless charging coil.